(untitled) (Fiep Bulletin - online, 2014)
The search for leisure activities is present since humankind was born, and such activities are distinct according to the culture of each society. The present paper analyzes different approaches of leisure, bringing it under the light of several researchers and portraying it in several societies and epochs, comparing it with different social classes, and also approaching leisure in contemporary context, in an analogy with previous epochs. It is concluded that leisure is accessible to only part of population and, despite the reduction of working hours and technological advances, only a small part of the free time is fulfilled with activities characterized as leisure.